Cefixime; a cephalosporin antibiotic, triggers mitochondrial-mediated cell death via mitochondrial permeability transition pore opening in male Wistar rats (African Journal of Biomedical Research, 2024)
Background: Inducers or inhibitors of opening of the Mitochondrial Permeability Transition (mPT) Pore are targets of drug development for conditions arising from dysregulated apoptosis. Some antibiotics have been shown to effect anticancer property by induction of mitochondrial-mediated cell death via mPT pore opening. This study therefore investigated the effect of cefixime; a cephalosporin antibiotic on mitochondrial-mediated cell death via mPT pore using rat model.Methods: Thirty male Wistar strain rats were randomly assigned into five equal groups; group I is the control while groups II, III, IV and V were orally treated with cefixime (10, 20, 30  and 40mg/kg) daily for two weeks. Mitochondria were isolated by differential centrifugation. The opening of the pore, cytochrome c release, mitochondrial ATPase (mATPase) activity, mitochondrial lipid peroxidation (mLPO), caspases 3 and 9 activities and hepatic DNA fragmentation were determined.Results: Varying concentrations of cefixime caused induction of mPT pore opening, cytochrome c release and mATPase activity in a concentration-dependent manner. Similarly, oral administration of cefixime caused dose-dependent induction of mPT pore opening, mATPase activity, mitochondrial lipid peroxidation (mLPO) and caspases 3 and 9 activation and hepatic DNA fragmentation.Conclusion: These results suggests that cefixime; a cephalosporin antibiotic, triggers mitochondrial-mediated cell death via mitochondrial permeability transition pore opening in male Wistar rats. Its anticancer potential should further be explored